pH Stress Mediated Alteration in Protein Composition and Reduction in Cytotoxic Potential of Gardnerella vaginalis Membrane Vesicles - Shishpal, Parul; Patel, Vainav; Singh, Dipty; Bhor, Vikrant M. (Frontiers in Microbiology, 2021)
The vagina of healthy women which is predominantly colonized by lactobacilli also harbours limited proportion of certain anaerobes such as Gardnerella vaginalis. An increase in G. vaginalis along with other anaerobes on account of perturbation in the vaginal micro-environment is associated with bacterial vaginosis (BV). Although strategies adopted by G. vaginalis for survival and pathogenesis in a conducive environment i.e. high vaginal pH, characteristic of BV, have been previously studied, the approaches potentially employed for adaptation to the low pH of the healthy vagina are unexplored. In the present study, we investigated the effect of acidic stress on the modulation of the production and function of membrane vesicles of G. vaginalis. pH stress led to a distortion of the bacterial cell morphology as well as an altered biogenesis of membrane vesicles, as revealed by transmission electron microscopy (TEM). Both qualitative and quantitative differences in protein content of MVs produced in response to pH stress were observed by flow cytometry. A significant change in the protein composition characterized by presence of chaperones despite a reduction in number of proteins was also noted in the stress induced MVs. Further, these changes were also reflected in the reduced cytotoxic potential towards vaginal epithelial cells. Although, these findings need to be validated in the in vivo settings, the modulation of G. vaginalis MV biogenesis, composition and function appears to be in concordance with host physiology in the absence of vaginal infection.